Physiological Intraocular Pressure in Cataract Surgery: A Comparative Consecutive Case Series Study - Sarossy A; Chakrabarti R (Clinical Ophthalmology, 2025)
Alexander Sarossy,1,2 Rahul Chakrabarti1– 4 1Essendon Eye Clinic, Essendon, Victoria, Australia; 2Faculty of Medicine, Nursing, Health Sciences, Monash University, Clayton, Victoria, Australia; 3The Royal Victorian Eye and Ear Hospital, Melbourne, Victoria, Australia; 4Department of Ophthalmology, The University of Melbourne, Parkville, Victoria, AustraliaCorrespondence: Alexander Sarossy, Faculty of Medicine, Nursing, Health Sciences, Monash University, PO Box 960, Moonee Ponds, Victoria, 3039, Australia, Email asar0045@student.monash.edu